Judicialização da saúde: tendências emergentes no sistema brasileiro e no direito comparado - Marques, Nathalia Oliveira (2017)
Research and investment, on the one hand, a constitutional guarantee of the law to health and its accessibility, and, on the other hand, the dilemmas and difficulties of public health in Brazil, passing through an analysis of the current Brazilian health system, while It also considers health systems implemented in other nations around the world, detecting problems and seeking solutions. Since, for the most part, the instrument of guaranteeing health rights is not effective - when it is not depleted by public administration practices - there are also comments about a guarantee of access to fair, a phenomenon called Health Judicialization and how this scenario has developed without a world scenario, considered as particularities of different countries. Thus, here a judicialization of health is taken as an instrument of presumed affront to the principle of reserving the benefit and balance of public accounts. There is therefore a eventual normative and principle-wise conflict between, on the one hand, the constitutionally guaranteed right to health, irresponsible access to the judiciary and, in the other hand, the reservation of the assembly and the allocation of public funds. Based on the assumption that the constitutional text determines that the social rights foreseen in the sixth article are materialized through social and economic policies (Article 196) and demand public expenditure that must be foreseen without public budget, it is concluded that any modification or distortion of public policy implies the disorganization of public finances. When, however, an effectiveness of social rights, especially the right to health, operates through the judiciary, there is an expansion of public policy and therefore of expenditure, as soon as this expenditure is repeated for a considerable period and, despite this, is not a part of the budget provision, besides the disorganization of the public finances of the disabled resources, repercussing without the right to collective attention. In addition, electronic and legal demonstrations to protect the right to health, an unweaneability of the judiciary, explore the possible normative conflict between the right to health and the principle of possible reserving and scarce public resources, ending up the common study with an analysis of judicialization and comparative law at the level of legal and comparative order . Research and investment, on the one hand, a constitutional guarantee of the law to health and its accessibility, and, on the other hand, the dilemmas and difficulties of public health in Brazil, passing through an analysis of the current Brazilian health system, while It also considers health systems implemented in other nations around the world, detecting problems and seeking solutions. Since, for the most part, the instrument of guaranteeing health rights is not effective - when it is not depleted by public administration practices - there are also comments about a guarantee of access to fair, a phenomenon called Health Judicialization and how this scenario has developed without a world scenario, considered as particularities of different countries. Thus, here a judicialization of health is taken as an instrument of presumed affront to the principle of reserving the benefit and balance of public accounts. There is therefore a eventual normative and principle-wise conflict between, on the one hand, the constitutionally guaranteed right to health, irresponsible access to the judiciary and, in the other hand, the reservation of the assembly and the allocation of public funds. Based on the assumption that the constitutional text determines that the social rights foreseen in the sixth article are materialized through social and economic policies (Article 196) and demand public expenditure that must be foreseen without public budget, it is concluded that any modification or distortion of public policy implies the disorganization of public finances. When, however, an effectiveness of social rights, especially the right to health, operates through the judiciary, there is an expansion of public policy and therefore of expenditure, as soon as this expenditure is repeated for a considerable period and, despite this, is not a part of the budget provision, besides the disorganization of the public finances of the disabled resources, repercussing without the right to collective attention. In addition, electronic and legal demonstrations to protect the right to health, an unweaneability of the judiciary, explore the possible normative conflict between the right to health and the principle of possible reserving and scarce public resources, ending up the common study with an analysis of judicialization and comparative law at the level of legal and comparative order.